PROTECTIVE EFFECT OF CAMELLIA OLEIFERA ABEL. ON SILICA-INDUCED PULMONARY FIBROSIS IN RATS - Tian, Shenglan; Liu, Xiaoliu; Yang, Yang; Lv, Yang (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Camellia oleifera Abel. belongs to the family Theaceae and genus Camellia. It is commonly cultivated in southern China. The seeds of C. oleifera have been reported to exhibit a diversity of pharmacological activities which include, but are not limited to, antioxidant, anti-cancer and antimicrobial. Pulmonary fibrosis is one of lethal causes of mortality across the globe and accretion of considerable amount of reactive oxygen species (ROS) in lungs have been implicated in the onset of this disease. Given the known antioxidant activity of C. oleifera seed extract (CSE), the present study was designed to evaluate the influence of CSE on the silica-induced pulmonary fibrosis rat models. Materials and Methods: Protective effect of CSE was determined in silica-induced pulmonary fibrosis rat models. Malondialdehyde (MDA), hydroxyproline (HP) and superoxide dismutase 2 (SOD-2) activity were determined by standard biochemical assays. Histopathological analysis was carried out by H and E staining. Phyto-constituents of CSE were identified by LC/MS analysis. Results: The results of this study indicated that CSE lowered the MDA and hydroxyproline content in silica-treated rats. Additionally, CSE also caused a significant increase in the expression of SOD-2 leading to scavenging of ROS. Hematoxylin and eosin (H and E) staining of lung tissue sections revealed that CSE maintained the integrity of parenchymatous cells of lungs and prevented the development of pulmonary fibrosis. To gain insights about the phytochemical constituents of CSE, LC/MS analysis was carried out and several antioxidant phenolics and flavonoids were tentatively identified. Conclusion: Taken together, we conclude that CSE prevents development of pulmonary fibrosis and the protective effect of CSE may be due to its ability to induce SOD-2 expression and due to the presence antioxidant phytoconstituents